#TITLE_ALTERNATIVE# - AHMAD SYAUQI HIDAYATILLAH (NIM : 12009020); Pembimbing, : Ir. Benyamin Sapiie, Ph.D.,
North Makassar Strait Basin is a part of Makassar Strait Basin that located at Western Part of Sulawesi Island. This basin have long been a concern among oil and gas company with its speculation about the existence of hydrocarbon in that area. The research took place at West Sulawesi Fold Belt that located in The Eastern Part of The North Makassar Strait Basin. The purpose of this research are to understand formation characteristic of The North Makassar Strait Basin especially at West Sulawesi Fold Belt, to analyze structural expression that happens, to calculate the amount of deformation, and to understand the formation history of the basin through time structure map and palinspatic reconstructions. The data used in this research consist of two dimension seismic data, checkshot data, and well log data. The method consist of analyzing structure cross sections, analyzing time structure maps, analyzing isochron maps, and palinspatic reconstructions. Seismic data interpretation showed that formation of research area characterized by two tectonic regime: extensional and contractional regime. Extensional regime characterized by the presence of grabens and half-grabens structures in the basement. Whereas contractional regime characterized by fold-thrust belt involving younger strata. Based on structural pattern and style interpretation seismic data suggest that research area can be divided into three structural provinces: North, Middle, and South. The concentration of fold-thrust belt at the North and South of research area are interpreted as results of basement morphology and sediment thickness. Palinspatic reconstructions showed that research area have been deformed with lengthening 25,28% and shortening 13,68%, with total strain of 11,6%. The history of basin formation of research area begins with basement as pre-rift rifting at Middle Eocene that based on structural pattern is oblique rifting, occured depositing syn-rift sediment, and stopped at Late Eocene. Then at Oligocene deposited carbonate rocks accompanied with thermal subsidence. This thermal subsidence continued during Early Miocene until Late Miocene, that based on structural pattern and seismic reflector characterization showed post-rift sedimentation. At Pliosen until recent, occured the formation of fold-thrust belt that resulted by collision of Banggai-Sula Microcontinent and East Sulawesi. This fold-thrust belt formation accompanied with sedimentation between the folds forming syn-kinematic basins.